Magnetic structures and electronic properties of cubic-pyrochlore ruthenates from first principles. (11th May 2022) - Huebsch, M-T; Nomura, Y; Sakai, S; Arita, R
Abstract: The magnetic ground states of R 2 Ru2 O7 and A 2 Ru2 O7 with R = Pr, Gd, Ho, and Er, as well as A = Ca, Cd are predicted devising a combination of the cluster-multipole (CMP) theory and spin-density-functional theory (SDFT). The strong electronic correlation effects are estimated by the constrained-random-phase approximation (cRPA) and taken into account within the dynamical-mean-field theory (DMFT). The target compounds feature d-orbital magnetism on Ru 4+ and Ru 5+ ions for R and A, respectively, as well as f-orbital magnetism on the R site, which leads to an intriguing interplay of magnetic interactions in a strongly correlated system. We find CMP + SDFT is capable of describing the magnetic ground states in these compounds. The cRPA captures a difference in the screening strength between R 2 Ru2 O7 and A 2 Ru2 O7 compounds, which leads to a qualitative and quantitative understanding of the electronic properties within DMFT.